2015
DOI: 10.12659/msm.893520
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Training Improves New Mothers’ Understanding of Jaundice

Abstract: BackgroundMothers’ knowledge of neonatal jaundice (NNJ) is grossly deficient or inaccurate, which may adversely affect the actions of mothers in the recognition of NNJ and cause a delay in seeking medical attention.Material/MethodsA total of 1036 primiparas were separated randomly into the intervention group and the control group, with 518 primiparas in each group.ResultsAll (100%) mothers in the intervention group understood that NNJ is a yellow discoloration of the skin and sclera; 94.19% of them considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…This study found that women could insist on continuing breastfeeding despite their physical discomfort or the impact from neonatal jaundice during the first week after birth. The finding was differed from that of previous studies, which showed that mothers stopped breastfeeding when and after their neonates had breastfeeding or breast milk jaundice [23]. In the contemporary breastfeeding-friendly environment, it was found that mothers did not need to stop and could continue breastfeeding.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…This study found that women could insist on continuing breastfeeding despite their physical discomfort or the impact from neonatal jaundice during the first week after birth. The finding was differed from that of previous studies, which showed that mothers stopped breastfeeding when and after their neonates had breastfeeding or breast milk jaundice [23]. In the contemporary breastfeeding-friendly environment, it was found that mothers did not need to stop and could continue breastfeeding.…”
Section: Discussioncontrasting
confidence: 84%
“…They may have found it too overwhelming to learn about neonatal jaundice effectively at that time. Previous research showed that prenatal training could significantly help mothers understand neonatal jaundice [29]. This finding suggests that information about neonatal jaundice should be provided in prenatal health education for pregnant women who intend to breastfeed to improve knowledge and perceptions of breastfeeding and breast milk jaundice and reduce anxiety among postpartum women.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…4 Jaundice, which occurs within the first 36 hours and lasts more than 2 weeks, accounts for 82.8% and 95.27%, respectively. 5 Neonatal sepsis (66.7%), prematurity (15.2%), lack of breastfeeding (9%), and ABO incompatibility (5.2%) were the leading causes of neonatal jaundice. 6 In Africa, the incidence of severe neonatal jaundice accounts for 667.8 per 100 000 live births, which is higher than the incidence in Southeast Asia, the Eastern Mediterranean, the Western Pacific, America, and the European regions.…”
Section: Introductionmentioning
confidence: 99%
“…Improved maternal knowledge does not always translate into improved care-seeking practices for neonatal jaundice. Nonetheless, several studies have demonstrated that maternal education has favorable impact on maternal recognition and care-seeking practices for neonatal jaundice [ 12 , 25 , 29 , 34 ]. Better understanding and empowerment will likely prevent most mothers from overlooking the potential risks of untreated or lately treated significant jaundice such as mortality and life-long disability in otherwise healthy newborns.…”
Section: Discussionmentioning
confidence: 99%